2020
DOI: 10.1155/2020/7834252
|View full text |Cite
|
Sign up to set email alerts
|

Downregulated Recycling Process but Not De Novo Synthesis of Glutathione Limits Antioxidant Capacity of Erythrocytes in Hypoxia

Abstract: Red blood cells (RBCs) are susceptible to sustained free radical damage during circulation, while the changes of antioxidant capacity and regulatory mechanism of RBCs under different oxygen gradients remain unclear. Here, we investigated the changes of oxidative damage and antioxidant capacity of RBCs in different oxygen gradients and identified the underlying mechanisms using an in vitro model of the hypoxanthine/xanthine oxidase (HX/XO) system. In the present study, we reported that the hypoxic RBCs showed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Previous studies have confirmed that Band 3 has a vital role in maintaining the structural stability and mechanical properties of RBCs by linking phospholipid bilayer and spectral-based skeletal networks ( 23 , 33 ). Band 3 cluster caused by OS is usually accompanied by a decrease in the deformability of RBCs ( 19 , 34 ).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Previous studies have confirmed that Band 3 has a vital role in maintaining the structural stability and mechanical properties of RBCs by linking phospholipid bilayer and spectral-based skeletal networks ( 23 , 33 ). Band 3 cluster caused by OS is usually accompanied by a decrease in the deformability of RBCs ( 19 , 34 ).…”
Section: Discussionmentioning
confidence: 83%
“…ab150077; Abcam). After being washed three times in PBS, fluorescence images were captured using an Olympus IX71 fluorescence microscope (Olympus Corporation) ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…P0006; Beyotime Institute of Biotechnology). Western blot analyses were performed as previously described ( 20 ). Briefly, sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) was performed by heating the samples for 8 min at 100˚C and loading 10 µg membrane proteins on to a 5-15% linear acrylamide gradient gel (10 µg protein/lane).…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analyses were performed as described previously ( 22 ). Briefly, after SDS-PAGE, proteins were electro-transferred to PVDF membranes and blocked in 5% BSA dissolved in TBST for 2h at room temperature.…”
Section: Methodsmentioning
confidence: 99%